A que(m) serve a música na reforma psiquiátrica brasileira?: Linhas de audibilidade nas práticas musicais da saúde mental coletiva - Cardoso, Tânya Marques [UNESP] (2014)
In this paper, we discussed some perspectives of the relation between music and subject, in the context of the Brazilian Psychiatric Reform and in Collective Mental Health practices, specifically, musical and sound practices. We were inspired by the archeogenealogy to create some methodological tools for this work. To our question of to what or to who the music serves in the Psychiatric Reform, the answer was the bibliographic organized in a File – web, tool that we forged from the notion of archeogenealogy combined with that of device, from the work of Foucault. The web we built, like a piece of the device, has lines of statements and visibilities that intersect to support certain discourses and occupy certain roles each season. We sought, first, to problematize this space where the web is suspended, in the actions with music in the context of the hospices, following the logic of hygienism and disciplining of bodies. With the modernist experiences, it was constituted an important contrast between the field of psychiatric knowledge and that of artistic creation. Music therapy is also investigated in its history, considering that it has a common origin to the musical and sound practices in general, beyond the fact of representing a specific knowledge about music- subjectivity-health relation. Then, we envisioned how the music and sound practices served the anti-asylum and how they were incorporated into the Brazilian Psychiatric Reform as policies, from the concept of workshops, within the logic and ethics of deinstitutionalization, the Paradigm of Psychosocial Care and the idea of “saúdessubjetividade/subjetividadessaúde”. From various documentary sources - books, journals, electronic databases and electronic sites – we found unique experiences of musical practices, which we called strings or threads of the web which were arranged from its working processes: 1. music-therapy; 2. Music ...